Study of the biochemical effects induced by X-ray irradiations in combination with gadolinium nanoparticles in F98 glioma cells: first FTIR studies at the Emira laboratory of the SESAME synchrotron. Issue 7 (2nd March 2016) - Yousef, Ibraheem; Seksek, Olivier; Gil, Sílvia; Prezado, Yolanda; Sulé-Suso, Josep; Martínez-Rovira, Immaculada
Abstract : One strategy to improve the clinical outcome of radiotherapy is to use nanoparticles as radiosensitizers. Abstract : One strategy to improve the clinical outcome of radiotherapy is to use nanoparticles as radiosensitizers. Along this line, numerous studies have shown the enhanced effectiveness of tumour cell killing when nanoparticles are exposed to irradiation. However, the mechanisms of action are not clear yet. In addition to the damage due to a possible local radiation dose enhancement, the interaction of nanoparticles with essential biological macromolecules could lead to changes in the cells, such as cell arrest at radiosensitive phases. Within this framework, vibrational spectroscopy was used to investigate the biochemical changes in F98 glioma cells induced by X-ray irradiations combined with gadolinium nanoparticles. Fourier transform infrared (FTIR) microspectroscopy experiments were performed at the Emira laboratory of the SESAME synchrotron (Jordan), allowing the characterisation of spectral signatures of nanoparticle-induced effects in glioma cells. Multivariate analysis of the spectra recorded using principal component analysis reveals clear differences in the DNA, protein and lipid regions in the presence of nanoparticles. Prior to irradiation, results show that nanoparticles induce biochemical modifications in the cells, probably due to changes in the cellular function. Biochemical alterations are amplified in the presence of radiation. In particular, variations in the intensity and in the position of the PO2 − symmetric and asymmetric modes are observed due to radiation damage to the DNA, which is increased in nanoparticle-treated cells. At 24 hours post-irradiation, biochemical changes related to the hallmark characteristics of cell death are detected. This includes a shift towards low wavenumbers in the amide I and II bands, relative amplitude changes in the CH2 and CH3 stretching modes, along with DNA chromatin condensation indications. Results were confirmed by two complementary cell viability assays.